2022
DOI: 10.1038/d41586-022-00584-8
|View full text |Cite
|
Sign up to set email alerts
|

Wuhan market was epicentre of pandemic’s start, studies suggest

Abstract: cientists have released three studies that reveal intriguing new clues about how the COVID-19 pandemic started. Two of the reports trace the outbreak back to a massive market that sold live animals, among other goods, in Wuhan, China 1,2 , and a third 3 suggests that the coronavirus SARS-CoV-2 spilled over from animalspossibly those sold at the market -to humans at least twice in November or December 2019. Posted on 25 and 26 February, all three are preprints, and so have not been published in a peer-reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 7 publications
0
28
0
3
Order By: Relevance
“…She says that says that although the scientific consensus seems to be that SARS-CoV-2 originated at a market in the city of Wuhan,9 earlier laboratory acquired coronavirus infections are a reminder that such infections do happen and “labs working with highly contagious and virulent pathogens have to be extraordinarily diligent and require competent third party oversight.”…”
Section: Education and Risk Managementmentioning
confidence: 99%
“…She says that says that although the scientific consensus seems to be that SARS-CoV-2 originated at a market in the city of Wuhan,9 earlier laboratory acquired coronavirus infections are a reminder that such infections do happen and “labs working with highly contagious and virulent pathogens have to be extraordinarily diligent and require competent third party oversight.”…”
Section: Education and Risk Managementmentioning
confidence: 99%
“…In fact, MERS-CoV prevalence in camels is very high, 80–99% depending on the country ( Omrani et al, 2015 ). SARS-CoV-2 has been most-likely transmitted to humans from racoons, as a virus with a 99.998% sequence identity to SARS-CoV-2 has been found in the feces present in the metal cages of the Huanan market at Wuhan ( Gao et al, 2022 ; Holmes et al, 2021 ; Maxmen, 2022 ; Pekar et al, 2022 ; Worobey et al, 2022 ).
Fig.
…”
Section: Human Covs Originmentioning
confidence: 99%
“…However, misinformation surrounding the Covid-19 has been a distinctive feature of this pandemic since its very beginning in Wuhan in late 2019. [10] For instance, in a sample of statements about the coronavirus rated false or misleading by fact-checkers between January and March 2020, it was found that 59% of misinformation was created by reconfiguring and recontextualizing information and 38% was entirely fabricated. [11] Here the term misinformation stands for inaccurate information that can can mislead and harm people, regardless of whether it results from an honest mistake, negligence, or intentional deception.…”
Section: Introductionmentioning
confidence: 99%